Let g the inverse function of f.
The most important property of g and f being inverses of each other, is that
g(f(x))=x, also f(g(x))=x
so, what one function 'does' to x, the other 'undoes' it.
Thus, we have:
f(g(x))=x and alos f(g(x))= -g(x)+3, from the rule
thus :
-g(x)+3=x
-g(x)=x-3
g(x)=-x+3
check: f(g(x))=f(-x+3)=-(-x+3)+3=x-3+3=x
Answer: the inverse of f is g, such that g(x)=-x+3
Can you add more information?
20%, because if 65 is 100, then 52 is 80% out of 65; so 100 - 80 is 20
It is 6 because 6x6x6=216
The answer is 4.5 miles. Hope it helps!